EFFECTS OF AL MICRO-BUMPS ON THE MAGNETIC-PROPERTIES AND MORPHOLOGY OF COCRTA/CR/AL THIN-FILMS - CHANG, HS; SHIN, KH; LEE, TD; PARK, JK (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 1995)
CoCrTa thin films were deposited on glass substrates at various temperatures with or without. Al micro-bumps. The coercivity of the CoCrTa thin films increased considerably by introducing the Al micro-bumps as a texture layer. The cause of the coercivity increase was attributed to the development of strong Co(10 (1) over bar 0) texture and refinement of Co grains induced by small Cr grain when the films were deposited on the Al bumped substrates. The morphology of the CoCrTa/Cr/Al thin films was very sensitive to the Al micro-bump distributions.
Keywords: UNDERLAYERS; TEXTURE